Socjalistyczny w formie, narodowy w treści. Chorwacka odmiana komunistycznej nowomowy w czasie tzw. chorwackiej wiosny - Czerwiński, Maciej (Stylistyka, 2020)
In this article the problem o f Yugoslav Newspeak, in the Croatian version that appeared in the period o f the so-called Croatian Spring (1971), is taken into consideration. The aim of the analysis is to demonstrate how Croatian national values and beliefs - understood in semiotic terms as a ‘m onal codę’ - were conveyed within the rigid and inflexible communist discourse (understood as a ‘communist codę ). Thus, the Stalinist slogan “National in form, socialist in content” is dcliberately shifted into “Socialist in Form and National in Content”. This shift aims at demonstrating that the Croatian elite took advantage of the communist Newspeak in order to explicate its own national consciousness without being accused of anti-Serbian nationalism, or de stroying the idea o f “brotherhood and unity”. The interrelation of the two codes brings about a very complex linguistic phenomenon. In the article the analysis concems several problems: (1) the semiotic capacity of the genre that enablcd one to convey national values without questiomng Yugoslav unity, (2) discursive formations hringing about sensitive relations hetween Croats and Serbs, including certain semantic and formal strategies, and (3) the issue o f the purist consciousness with respect to Newspeak. The article demonstrates that the communist political leaders play an important role re-establishing independent Croatian discourse. This stratégy is not limited to Croatia sińce in all of the former socialist republics o f the Yugoslav I cderal >n the same situation occurred.